Platelet-Rich Plasma (PRP) for Acute Muscle Injury: A Systematic Review - Hamid, M.S.A. (Public Library of Science, 2014)
Introduction Acute muscle injury is one of the commonest injuries that often result in loss of training and competition time. The best management for muscle injury has not been identified. Sports medicine practitioners used several approaches in attempt to accelerate time to recovery from muscle injury. More recently growing interest focussed on autologous blood product injection.